Does the Digital Payment System “QRIS” Affect the Purchasing Behaviour of Food and Beverage Products? - Safitri, Ajeng Rahma; Ningrum, Roro Aditya Citraningtyas (Ilomata International Journal of Management, 2024)
This study analyzes whether the availability of the QRIS payment method influences the decision to purchase food or drink products for people who are familiar with this payment method. Data was collected through an online survey (n = 112) and followed by respondents in the age range 18-45 years who live in the city of Jakarta and its surroundings as well as several other provinces. Survey questions were developed by adopting some of the factors in innovation adoption (E.M. Rogers, 1972) and factors that influence purchasing behavior (Widayat, Marsudi and Ilyas Masudin, 2023). Based on the simultaneous test and partial test, the probability F-statistics value and the significance value of the QRIS payment system variable is smaller than α (0.05), showing that there is a significant effect of the QRIS payment system on the purchasing behavior variable. A simple regression analysis was carried out, which was also accompanied by a normality test, linearity test and hypothesis test. As a result, the coefficient of determination reveals an R squared value of 0.281, which means that the QRIS payment system variable is able to influence purchasing behavior variables by 28.1%. The results of this research provide insight to business actors, business practitioners and policy makers in the banking sector that convenience in transactions needs to be considered as part of an effective marketing strategy.